PENGARUH PENAMBAHAN FRUKTO-OLIGOSAKARIDA (FOS) PADA MP-ASI TERHADAP KEJADIAN DIARE DAN PERTUMBUHAN BAYI UMUR 6-12 BULAN (Studi eksperimen lapangan di Kabupaten Bogor, Jawa Barat) - Widjojo, Sunarno Ranu; F, Agus; Utomo, Budi; L. Achadi, Endang (PERSATUAN AHLI GIZI INDONESIA, 2006)
THE EFFECT OF FOS SUPPLEMENTATION TO COMPLEMENTARY FEEDING IN DIARRHEA CASES AND GROWTH IN BABY 6-12 MONTHThe overall objective of this study was to evaluate the impact of adding fructo oligosaccharides (FOS) to complementary foods on the frequency and duration of diarrheal episodes and physical growth of 6-12 month old infants. The study was a double-blind randomized controlled trial carried out in the District of Bogor, Indonesia in 2004. Enrollees were 6-month old infants. Subjects were allocated to one of three study groups: Group FOS 4.0 received complementary food (CF) with 4.0% FOS added, Group FOS 3.2 received CF with 3.2% FOS, and Group FOS 0.0 received CF with no FOS. Infants received CF daily during the 6-month duration of the study. Among 192 infants enrolled, 163 had complete data for analysis. The results of the analysis on the cumulative number of general episode of diarrhea showed that only the FOS 3.2 group had significantly fewer episodes than the FOS 0.0 group with 1.10±1.30 episode and 1.73±1.90 episode respectively (p=0,02). Analysis on the number of episodes with =2 days of duration of diarrhea showed both FOS 4.0 and FOS 3.2 groups had significantly fewer episodes than the FOS 0.0 group, with 0,62+0,97 for the FOS 4.0 group, 0,62±1,17 for the FOS 3.2 group, and 1,21±1,59 for the FOS 0.0 group (P=0,02). The significant effect of FOS appeared after 4 months of intervention and continued up to 12 months of age. The analysis showed no significant effect of FOS on the cumulative duration of diarrhea and on the physical growth of the babies.Keywords: babies, MP-ASI, FOS, diarrhea, and physical growth